Effect of Microwave Treatment on the Profile of Volatile Compounds and Characteristics of White Pepper (Piper nigrum L.) Essential Oil - Atma Elfahdi (Universitas Bangka Belitung, 2021)
Microwave treatment on white pepper was conducted to damage cell tissue to facilitate the distillation and increase the yield of essential oils. The research objective was to determine the effect of pepper varieties and microwave treatment on the profiles of volatile compounds and the characteristics of white pepper essential oils. The research was conducted with 50 grams of white pepper placed into a 15 cm diameter petri dish and put in a microwave oven at the power of 600 watts for 90 seconds then white pepper milled by hammer mill. Essential oils were obtained using the water distillation method then were tested for their characteristics and compounds using Gas chromatography-Mass Spectrometry (GC-MS). White pepper was analyzed using the water content, piperine content, and its cell tissue microstructure was analyzed using Scanning Electron Microscope (SEM). The results showed that different pepper as accession produced different profiles of volatile compounds, characteristics, and antioxidant activity (p<0.05). The number of volatile compounds of white pepper essential oils identified by GC-MS was 42, where the largest compound was β-caryophyllene (50.51%). Microwave treatment damaged the cell wall of white pepper, lowered water content (17.43%), increased piperine content (10.57%) and essential oil yield (25%), and changed the profiles of volatile compounds of essential oils of Lampung daun lebar accession. Color became bluer (b*value rises by 201.99%), increased specific gravity (1.27%) and antioxidant activity (7.4%), decreased solubility in 95% ethanol (17.95%) and acid number (20.8%) while the refractive index was not affected by pepper accessions and microwave treatment.